2018
DOI: 10.5812/sdme.85046
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Disposition in the First- and Last-Year Medical Students and its Association with Achievement Goal Orientation

Abstract: Background: Since medical students play an important role in public health system as well as the treatment of patients, the need for critical thinking in them is extensively felt. The current study aimed at evaluating the level of critical thinking disposition (CTD) in the first-and last-year medical students and its association with goal orientation in Ahvaz Jundishapur University of Medical Sciences in 2016. Methods: The current cross sectional study used critical thinking disposition inventory (CTDI) develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
2
Order By: Relevance
“…The results of the current study were in line with the findings of the studies by Barkhordary, Shakurnia and Baniasad, Athari, and Kaya et al which did not report any significant difference among critical thinking disposition and years of education. [ 10 13 14 15 ] However, our results are not in line with those of Taheri et al [ 12 ] and Mslm[ 27 ] which reported an ascending trend between critical thinking disposition and years of education and those of Fathiazar et al [ 16 ] and Huang et al [ 28 ] which reported a descending trend. These discrepancies can be the result of factors such as training environment, training method, methods of assessment, and various cultural factors.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The results of the current study were in line with the findings of the studies by Barkhordary, Shakurnia and Baniasad, Athari, and Kaya et al which did not report any significant difference among critical thinking disposition and years of education. [ 10 13 14 15 ] However, our results are not in line with those of Taheri et al [ 12 ] and Mslm[ 27 ] which reported an ascending trend between critical thinking disposition and years of education and those of Fathiazar et al [ 16 ] and Huang et al [ 28 ] which reported a descending trend. These discrepancies can be the result of factors such as training environment, training method, methods of assessment, and various cultural factors.…”
Section: Discussioncontrasting
confidence: 98%
“…Some studies have reported an increasing trend in the level of students “critical thinking and some other studies have reported a lack of difference in the level of students” critical thinking in different years and a descending trend. [ 12 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a study conducted on medical students of Gonabad/Iran, the mean score of critical thinking disposition (143.57 ± 23.59) [ 37 ] was higher than in the current study; unlike the present study, the highest mean was related to commitment and the lowest mean pertained to innovation [ 37 ]. The mean score of critical thinking disposition in medical students of Jundishapour/Iran was 70.75 ± 11.12, and the highest and lowest means, respectively, were related to the dimension of mental engagement and innovation [ 38 ]; this is inconsistent with the results of the present study. This disparity can be attributed to differences in research communities, education, and culture.…”
Section: Discussioncontrasting
confidence: 98%
“…Medical sciences students must strengthen their critical thinking skills and disposition more than the students of other sciences (28). Unfortunately, studies have indicated that in most of the universities in Iran, the CTD level of students is rather low and undesirable (23,29,30). Therefore, special attention must be paid to the attitudes of professors toward critical thinking skills and their teaching methods of choice, as well as educational programs.…”
Section: Discussionmentioning
confidence: 99%